Integrating on-premises data with customer relationship management application on cloud: A hybrid IT infrastructure support service. Issue 1 (1st January 2018) - Chiranjeevi, H. S.; Shenoy, Manjula K.; Sundar, D. Syam
Abstract: Customer relationship management (CRM) is a group of data-driven, integrated solution that enhances how an organization interacts and does business with the customers. University support service centres provide hone support for the university stakeholders' queries and requests related to academic information. The support centre uses retrieval of information from huge text documents, records, and log files from disparate data sources residing on on-premises. Handling data has become a critical task and moving all the data to the cloud is not feasible. The objective of designed hybrid solution is to serve a resolving customer service request and a scalable solution to a large set of data for the organizations concerned with security, efficiency, and to use the advantages of the cloud service. In the proposed hybrid solution, the data resides on the on-premises is connected to the customer relationship management application deployed on the cloud, this reduces the IT infrastructure tasks at a university support service. We describe the system's architecture and the technical challenges we have faced. The CRM application is deployed on Microsoft Azure cloud test instance and the Azure service bus relay is used to connect the on-premises data.